Battery System Sizing for 6.9 MWp Grid- Connected Photovoltaic System in UTHM - Bustamam, Nur Haziqah; Abdullah, Mohd Noor (Evolution in Electrical and Electronic Engineering, 2022)
RRenewable energies, such as photovoltaic system (PV) has recently gained popularity in the electrical industry. However, the fluctuating energy demand appears to have resulted in expensive electricity bills. Peak shaving is the most effective method for managing power bills for on-demand users and is used to eliminate short-term demand peaks that result in bigger demand peaks. Therefore, by using battery energy storage systems (BESS) for grid storage can reduce the wastage of electrical energy produced and improve efficiencies. The purpose of this project is to simulate a GCPV system located in Universiti Tun Hussein Onn Malaysia, Parit Raja and proposed a suitable battery storage system by using PVsyst software. Comparative studies of the two different strategies such as self-consumption (Selco) with and without battery energy storage have been carried out. Finally, the finding shows that solar power with battery storage is the best way to achieve the best performance. The battery itself does not cause pollution and does not affect business operations. They make solar energy beneficial to more customers, which in turn creates further savings